Training Programs And Their Impact On The Quality Of municipal Services /Field Research In The Municipality Of Baghdad - الزيدي, ناظم جواد; فاضل, عبد الرزاق عباس (Journal of Economics and Administrative Sciences, 2018)
The objective of this research is to measure the training programs and identify the nature and then measure how it reflected on the quality of municipal services provided by the municipal departments investigated by measuring the quality of services based on quality standards, the researcher chose four municipal departments in the Rusafa / Baghdad (164 people) representing the directors and their assistants, officials of the municipal departments, the people and the engineering staff in charge of the task forces as well, including the survey of the views of the concerned persons in the management of the Vocational Training Institute in the Secretariat of the Republic, The quality of the municipal services was measured through the dimensions of reliability, responsiveness, reliability, empathy, and motivation. They represent the paragraphs of the questionnaire. Prepared for this purpose. The data was collected through the questionnaire as well as the personal interviews of the stakeholders. The actual data obtained through the field experience and the personal and practical experience of the researcher. In addition to the questionnaire opinion (11) paragraph issued to citizens within the boycotted municipalities of the four surveyed, and for the purpose of data analysis and access to the results was used statistical software ready package (19- Ver-Spss) use ALL range of statistical methods descriptive, and research found a set of conclusions of the most important , That there is an important role played by training programs in achieving the quality of municipal services, through the benefits of these programs reflected positively on the quality of services is to increase motivation and also increase the skills of individuals and their ability to perform their functions better. There is also a significant correlation between the research variables. The results indicate that there is a significant correlation between the training programs in the quality of the municipal services. Based on the findings of the research results of the research, a number of recommendations were made. The human element is the most important components of the production elements, and this comes through the adoption of effective plans and programs for development, especially the engineers and technicians to provide them with knowledge and experience and change behavior towards achieving high quality service.